PENGARUH KONSENTRASI ABU VULKANIK GUNUNG MERAPI TERHADAP KUALITAS AIR DAN SINTASAN BENIH GURAMI (Osphronemus goramy) PADA TAHAP PENDEDERAN PERTAMA - , RIZKA ISNANTA P, Ir. Ign. Hardaningsih, M. Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of the study was to know the effect of Merapi volcanic ash concentrations on water quality and fry survival rate of giant gouramy (Osphronemus goramy) in the first nursery stage. The experimental method in this study used Completely Randomized Design that consisted of five volcanic ash (É¸ 0,5 mm) concentration treatments. The volcanic ash concentrations were sequentially at 0 mg/l, 50.000 mg/l, 100.000 mg/l, 150.000 mg/l, 200.000 mg/l. The experiment was conducted on 21 day old fry as much as 10 fishes per aquarium (in sizes 45 x 20 x 25 cm3) which cultured for 57 days. The water of the aquarium ( 18 liters volume ) were aerated. Tubifex sp. for feeding the fishes was 30% of the biomass weight per days. Result of the research showed that the higher Merapi volcanic ash concentration increased on water acidity, turbidity, hardness and sulfate, but were not affected on water temperature, dissolved oxygen, free carbon dioxide, alkalinity, total dissolved solids, total suspended solids, and ammonia. The higher Merapi volcanic ash concentration decreased on survival rate and absolute weight of giant gouramy fry, and damaged the gills lamela of fishes fry.